Concise Inorganic Chemistry - Lee, J. D. (London : Oxford University Press, 1964)
The fifth edition of this classic textbook has been extensively revised, but remains faithful to the principles that established it as a favourite among teachers and students around the world. The book is divided into six parts: theoretical concepts and hydrogen, the s-block, the p-block, the d-block, the f-block, and other topics (the nucleus and spectra). An important aspect of the book is its focus on the commercial exploitation of inorganic chemicals, something other textbooks do not cover, and this coverage has been expanded for the fifth edition. The treatment of the inorganic aspects of environmental chemistry has also been extended.
Keywords: Inorganic chemistry